Associations of diarrhea episodes and seeking medical treatment among children under five years: Insights from the Zimbabwe Demographic Health Survey (2015–2016). Issue 11 (21st September 2021) - Musuka, Godfrey; Dzinamarira, Tafadzwa; Murewanhema, Grant; Cuadros, Diego; Chingombe, Innocent; Herrera, Helena; Takavarasha, Felicia; Mapingure, Munyaradzi
Abstract: Diarrhea is a significant pediatric public health concern globally and places a significant burden on healthcare systems. In resource‐limited settings, the problems of diarrhea could be worse than reported. Continuously monitoring and understanding the changing epidemiology of diarrhea, including risk factors, remain an important aspect necessary to design effective public health interventions to reduce the incidence, outcomes and strain on healthcare resources caused by diarrheal illness. We, therefore, undertook this study to understand the factors associated with diarrhea as well as describe determinants for seeking medical treatment in children under‐five in Zimbabwe using the Zimbabwe Demographic and Health Survey 2015–2016 Data. Children with recent diarrhea were on average younger (mean age 22 months), compared to those who did not have an episode of diarrhea (mean age 30 months) p  = .001. Incidence of recent diarrhea was lower among female children compared to their male counterparts (16% vs. 19%), p  = .013. Incidence of diarrhea decreased with increasing maternal education level and so was the same for increasing wealth quintile. Those with unimproved sources of drinking water had a higher incidence of diarrhea. The wealth quintile remained the only factor associated with seeking medical attention for a recent diarrhea episode among children less than 6 years, with those in the highest wealth quintile being 2.49 times likely to do so, p  = .031. The results are useful in informing pediatric public health policies and strategies for them to be successful in significantly reducing the incidence, morbidity, mortality and significant healthcare costs and burden to society associated with caring for children with diarrheal illnesses. Abstract : Diarrhea is a significant paediatric public health concern globally and places a significant burden on healthcare systems. Continuously monitoring and understanding the changing epidemiology of diarrhea, including risk factors, remains an important aspect necessary to design effective public health interventions to reduce the incidence, outcomes and strain on healthcare resources caused by diarrheal illness. We, therefore, undertook this study to understand the factors associated with diarrhea as well as describe determinants for seeking medical treatment in children under five in Zimbabwe using the Zimbabwe Demographic and Health Survey 2015–2016 Data.